2D Fillers Highly Boost the Discharge Energy Density of Polymer‐Based Nanocomposites with Trilayered Architecture. (14th July 2021) - Bai, Hairui; Zhu, Kun; Wang, Zhe; Shen, Bo; Zhai, Jiwei
Abstract: A new class of trilayered architecture blends polymer‐based nanocomposites with excellent discharge energy densities ( U dis ) is presented. The preferable energy storage performance is achieved in sandwich structured nanocomposite (PIP) films. The outer polarization‐layers (P‐layer) of the PIP film are composed of Sr2 Nb2 O7 nanosheets (SNONSs) as well as boron nitride nanosheets (BNNSs) dispersed in poly(vinylidene fluoride) (PVDF)/ polymethyl methacrylate (PMMA) blend polymer matrix (BPM) to provide high dielectric constant, while PVDF/PMMA with BNNSs forms the central insulation‐layer (I‐layer) to offer high dielectric breakdown strength ( E b ) of the resulting nanocomposite films. The dielectric performance, Weibull breakdown strength, and energy storage capacity of single and multi‐layer nanocomposites as a function of filler content are systematically examined. The evolution of electric trees is simulated via finite element methods to verify the experimental dielectric breakdown results in single layer nanocomposite films. The PIP film with optimized filler content displays a discharge energy density of 31.42 J cm −3 with a significantly improved charge–discharge efficiency of ≈71% near the Weibull breakdown strength of 655.16 MV m −1, which is the highest among the polymer‐based nanocomposites under the equivalent dielectric breakdown strength at present. Abstract : Energy storage performance is highly boosted in a new class of trilayered architecture poly(vinylidene fluoride) (PVDF)/polymethyl methacrylate (PMMA) blend polymer‐based nanocomposites by synergistically filling with 2D Sr2 Nb2 O7 nanosheets and boron nitride nanosheets. The large electric displacement (12.55 μC cm −2 ) near the Weibull breakdown strength (655.16 MV m −1 ) is obtained, which hence contributes a high discharge energy density (31.42 J cm −3 ).